2021
DOI: 10.1038/s41419-021-04358-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA-seq highlights a specific carcinoembryonic cluster in ovarian cancer

Abstract: Expounding the heterogeneity for ovarian cancer (OC) with the cognition in developmental biology might be helpful to search for robust prognostic markers and effective treatments. In the present study, we employed single-cell RNA-seq with ovarian cancers, normal ovary, and embryo tissue to explore their heterogeneity. Then the differentiation process of clusters was explored; the pivotal cluster and markers were identified. Furthermore, the consensus clustering algorithm was used to explore the different clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…After principal component analysis (PCA), the 24 most powerful PCs were used for t-distributed stochastic neighbor embedding (t-SNE) analysis for dimension reduction. Subsequently, cells were divided into fourteen clusters with a resolution of 0.5 by KNN analysis and the “FindClusters” method, and cell types were subsequently annotated by specific cell markers as previously described 30 32 . Finally, cell–cell communications among the cell types were investigated by the “CellChat” package 33 .…”
Section: Methodsmentioning
confidence: 99%
“…After principal component analysis (PCA), the 24 most powerful PCs were used for t-distributed stochastic neighbor embedding (t-SNE) analysis for dimension reduction. Subsequently, cells were divided into fourteen clusters with a resolution of 0.5 by KNN analysis and the “FindClusters” method, and cell types were subsequently annotated by specific cell markers as previously described 30 32 . Finally, cell–cell communications among the cell types were investigated by the “CellChat” package 33 .…”
Section: Methodsmentioning
confidence: 99%
“…They found that a pivotal malignant epithelial cluster, PEG10 + embryonic malignant epithelial (EME) cells, belonging to an intermediate stage of the embryo-to-tumor process, was associated with poor prognosis. Moreover, cell-specific marker genes of PEG10 + EME could well discriminate which patients would benefit from immunotherapy [ 40 ]. In the case of acute myeloid leukemia (AML) noted for ITH, researchers combined scRNA-seq and genotyping to characterize AML ecosystems and developed RF-based ML classifiers to predict AML cell types and distinguish malignant and normal cells in AML tumors.…”
Section: New Insights Into Cancer Immunotherapy Based On Ai-assisted ...mentioning
confidence: 99%
“…JSI-124 (cucurbitacin I), which targets the STAT3 signaling pathway, increases the cancer cell death rate and extent of disease response in vivo [ 47 , 48 ], suggesting that the JAK/STAT pathway could be a promising target for HGSOC treatment. In another recent study, scRNA-seq was performed using ovarian cancer, normal ovarian, and embryonic tissues to investigate heterogeneity [ 49 ]. This study showed a comparison of gene expression profiles between ovarian cancer and embryonic tissues.…”
Section: Single-cell Sequencing-matched Cancer Treatmentmentioning
confidence: 99%
“…This study showed a comparison of gene expression profiles between ovarian cancer and embryonic tissues. Interestingly, PEG10+ clusters have been identified in both ovarian cancer and embryonic tissues, which modulate cancer stem cell activity and drug resistance in ovarian cancer cells [ 49 ]. This study suggested that the PEG10-mediated cancer embryo population could be a therapeutic target for ovarian cancer.…”
Section: Single-cell Sequencing-matched Cancer Treatmentmentioning
confidence: 99%